Kesetaraan Gender Perspektif Islam (Studi Kasus di Pondok Pesantren Nurul Qodiri Lampung Tengah) - Indriyani Indriyani; Ehwanudin Ehwanudin; Rina Mida Hayati (Journal of Contemporary Islamic Education, 2024)
This research discusses gender equality implemented at the Nurul Qodiri Islamic Boarding School in Central Lampung and viewed from an Islamic perspective. In the background of this research, it is stated that gender is a cultural concept that is used to differentiate the roles, behavior, mentality and emotional characteristics of men and women that apply within society. Meanwhile, gender equality itself means equal opportunities for men and women to obtain their human rights as human beings and obtain appropriate roles in the nation and state. In Islamic studies, it is stated that there is no difference between men and women before God, but rather the level of faith and deeds of worship. Islam teaches its people to implement gender equality by mutual love and respect for fellow Muslim brothers. The purpose of this research is to study and investigate gender equality and how the concept of gender equality is implemented in the Nurul Qodiri Islamic Boarding School environment in Central Lampung. This research was conducted using a qualitative field approach method. The results of this research are that all male and female students at the Nurul Qodiri Islamic Boarding School in Central Lampung have received their respective rights as students and students, all existing activities can be participated in by all students, and all genders can also get the same positions and positions. in accordance with Islamic guidance and Islamic boarding school rules.